Development of Nutraceutical Spirulina-Moringa Oleifera (Nutrismo) Products as Natural Immunomodulator and Antioxidant Supplements - M Noris; Alkhair Alkhair; Juraidin Juraidin (Indonesian Journal of Global Health Research, 2026)
Phycocyanin research shows fluctuating trends and remains underexplored, particularly in its application for functional food and nutraceutical development, creating significant research gaps and opportunities for innovation such as NutrisMO This study aims to identify research trends and gaps in phycocyanin studies and to analyze factors influencing consumer intention to use NutrisMO, a nutraceutical product based on Spirulina and Moringa oleifera.A Systematic Literature Review (SLR) was conducted using the PRISMA approach with data sourced from Scopus (2005–2024), analyzed באמצעות VOSviewer and Leximancer. In addition, a quantitative explanatory study was conducted with 150 respondents selected through purposive sampling to review public acceptance of NUTRISMO products. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart-PLS. The SLR results indicate that research on phycocyanin is still limited and fluctuative, with identified gaps in food-related applications (21%), product-related challenges (8%), and C-phycocyanin concepts (6%), highlighting opportunities for further research and innovation. Meanwhile, the Smart-PLS analysis shows that all constructs meet validity and reliability criteria. Perceived Bioactive Content (β = 0.400), Health Awareness (β = 0.438), and Trust in Herbal Products (β = 0.440) significantly influence Perceived Benefit, which in turn strongly affects Intention to Use (β = 0.775). The model demonstrates moderate to strong explanatory power, with R² values of 0.513 for Perceived Benefit and 0.600 for Intention to Use. This study confirms that perceived benefit plays a crucial mediating role in shaping consumer intention to use nutraceutical products. It also emphasizes the need for further research on phycocyanin and supports the development of functional nutraceutical innovations like NutrisMO by integrating scientific evidence, health awareness, and consumer trust.